PENGARUH LIKUIDITAS, LOAN TO DEPOSIT RATIO DAN NON-PERFOMING LOAN TERHADAP RETURN ON ASSETS (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020) - Meylinda Haryati Putri; Wasti Reviandani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this research is to analysis the effect of Liquidity, Loan to Deposit Ratio and Non Performing Loans on Return on Assets in banking companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The approach used in this research is quantitative. The type of this research is descriptive quantitative. The nature of this research is explanatory. The population of this study is 40 conventional banking companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The samples used as research were 22 conventional commercial bank companies. The results of this study conclude that Liquidity has a significant effect on Return on Assets in banking companies listed on the Indonesian Stock Exchange for the 2016-2020 period. The Loan to Deposit Ratio has no effect on the Return on Assets of banking companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Non-Performing Loans have no significant effect on Return on Assets in banking companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Liquidity, Loan to Deposit Ratio and Non Performing Loans have a significant effect on Return on Assets in banking companies listed on the Indonesia Stock Exchange for the 2016-2020 period.